إصلاح نظام الزكاة بجمهورية المالديف : مشاكل وحلول - سعيد، محمد شهيم علي (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
The purpose of this research is to analyze the current zakah system in the Maldives, highlighting the issues related to it and providing a solution to those issues. Hence, a general introduction of the Maldives is provided including information relating to the country's religious, social and economic situation. The methods of collection and distribution of zakah and categories of wealth on which zakah was imposed historically in the past are discussed. The study also examines the establishment of the first Zakah Office in the Maldives and the system adopted in that office. The assignment of Zakah Office to the purview of the Supreme Council for Islamic Affairs and the responsibility upheld by the administrative offices in islands and atolls in collection and distribution of zakah are also discussed. The study also highlights the development of the Department of Zakah after the establishment of the Ministry of Islamic Affairs in 2008. The classical scholars' view of recipients of zakah, the view adopted by the Maldives and the view of the researcher are also highlighted. The study also analyzes the similarities and differences between zakah and tax, the reason for the introduction of tax in the Maldives, the ratios by which it is collected and the possibility of implementation of both zakah and tax system concurrently in an Islamic state like the Maldives. Furthermore, the view of Maldivian scholars on Islamic ruling on taxation is stated. Moreover, the role of the government on regulating the zakah system, the benefits to the society and the state and how a society should be when it is regulated are addressed. The study also analyzes the importance of establishing an independent body to regulate the zakah system in the Maldives and a model for such body is provided by the researcher. The research has found that the most pertinent issues in zakah system of the Maldives include lack of expertise, non-existence of regulatory framework and absence of an independent body. Finally, a model for regulating zakah system of the Maldives is proposed.